K voprosu o nedostatkach i protivorecijach sistemy podgotovki sportivnogo rezerva v Rossijskoj Federacii - Seyranov, S. G.; Bulgakova, N. Zh.; Evseev, S. P.; Fomichenko, T. G. (Vestnik sportivnoj nauki; Sports science bulletin, 2020)
The article observes the conditions for the formation of a modern system of training sports reserves in the Russian Federation.The authors of the article discuss the shortcomings and contradictions highlighted in the main report of the scientific and practical conference on improving the management model of youth sports, held by the Commission on physical culture and promotion of a healthy lifestyle of the Public Chamber of the Russian Federation on September 15, 2020. In conclusion, the authors consider it necessary to implement the proposed approaches to the development of the system of sports training (including youth sports) and physical education in the Russian Federation while making decisions that are strategically important for the country in the pilot project.